2023
DOI: 10.1128/spectrum.02416-22
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silage Diet on Meat Quality through Shaping Gut Microbiota in Finishing Pigs

Abstract: To avoid competition between people and animals for food, it is essential to develop nontraditional feeds. In this study, the effects of the silages of the unconventional feed resources mulberry and paper mulberry on meat quality of finishing pigs were examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…These four genera were restored after the MK-7 supplementation (all P < 0.05, Additional file 1 : Fig.S6A). Flexilinea belongs to the methanogens, which have been reported to be positively correlated with the increase of blood glucose and blood lipid parameters [ 33 ]; Escherichia-Shigella are the potentially pathogenic bacteria which have been correlated with the dysbiosis of microbiota [ 34 ]; and Lachnospiraceae are the family subset of the phylum Firmicutes which are known to be responsible for the production of SCFA [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These four genera were restored after the MK-7 supplementation (all P < 0.05, Additional file 1 : Fig.S6A). Flexilinea belongs to the methanogens, which have been reported to be positively correlated with the increase of blood glucose and blood lipid parameters [ 33 ]; Escherichia-Shigella are the potentially pathogenic bacteria which have been correlated with the dysbiosis of microbiota [ 34 ]; and Lachnospiraceae are the family subset of the phylum Firmicutes which are known to be responsible for the production of SCFA [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Clostridiales , Ruminococcaceae , Lachnospiraceae , and Eubacterium_coprostanoligenes_group are capable of bile acid 7alpha-dehydroxylation to produce SBAs, and these taxa were also showed an increasing trend after MK-7 intervention (Fig. 2 D, Additional file 1 : Fig.S3C, Fig.S5F) [ 35 , 58 61 ]. To the best of our knowledge, this is the first study to discover the association between MK-7 and increased synthesis of SBAs or SCFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Fermented mulberry leaves may also regulate lipid metabolism by regulating the intestinal flora and optimising the composition of short‐chain fatty acids in the intestine. Niu et al found that mulberry leaves can increase the content of short‐chain fatty acids, especially acetic acid, by affecting intestinal flora, thereby affecting lipid deposition (Niu et al, 2023). Related studies have found that mulberry leaf water extract can reduce the serum free fatty acid level in hyperglycemic mice (Han et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the relative abundance of norank_f_norank_o_Oscillospirales was notably lower in JZ compared to JC (p < 0.05). Notably, Terrisporobacter and Cellulosilyticum have been documented as effective cellulose degraders, contributing to enhanced feed digestion Cai and Dong, 2010;Niu et al, 2023).…”
Section: Effects Of Yps Addition On Donkey Gut Bacteriamentioning
confidence: 99%